The “Merdeka Belajar” Program as a Change in Education: Bibliometric Analysis - Eko Harianto (PT Ilmu Inovasi Nusantara, 2024)
In recent years, the “Merdeka belajar” program has attracted the attention of Indonesian experts. This study aims to perform a bibliographic analysis of several scientific journals since the inception of the “Merdeka belajar” program. A database retrieved from the Scopus website was searched for public publication, and the results were analysed with his BibExcel software and visualised with VOSviewer. Articles, including “Merdeka belajar” on the Scopus website, use English as the primary language of publication. The most published results in 2021 were “Merdeka belajar”. Therefore, a systematic review and meta-analysis of the content of the papers and variables identified on this topic is required. This will serve as a starting point for future research in this area and as a basis for future consideration of the development and progress of the “Merdeka belajar” program.